Zakat Produktif Sebagai Modal Kerja Usaha Mikro - Efri Syamsul Bahri; Reni Oktaviani (Perisai : Islamic Banking and Finance Journal, 2018)
Zakat is a duty ordered directly by Allah in the Qur'an. Zakat is well managed and able to empower mustahik as well as be a solution in alleviating poverty. The focus of this research is how to describe productive zakat as a micro business work capital and what are the benefits of productive zakat as working capital for mustahik? The purpose of this research is to dig deeper the model of productive utilization of zakat as working capital of micro business. The method used in this study is a qualitative method with a descriptive approach that describes a condition or fact finding with appropriate interpretation. The results of this study indicate that zakat institutions that apply the productive zakat model as a micro business work capital to be hope in improving social status mustahik be muzaki. Zakat as working capital is beneficial for empowering micro business, improving micro business business, growing spirit, improving ability and skill and entrepreneurship. Viewed from the socio-economic aspects of zakat can encourage the growth of the weak economy by increasing their purchasing power to increase employment and micro business income. Viewed from the moral-spiritual aspect of zakat is a means to increase obedience and servitude to God. Thus the productive zakat model as working capital becomes an effective way to alleviate poverty.